The Effect of Location and Price on Purchase Interest at Villa Kubu, Seminyak - Maharani, Ni Wayan Shinta; Sabudi, I Nyoman Sukana; Wiartha, Nyoman Gede Mas (PT FORMOSA CENDEKIA GLOBAL, 2024)
The high level of competition in the hospitality industry inevitably makes companies have to follow consumer tastes by understanding, and increasing buying interest. This study aims to determine the effect of location, price on buying interest in Villa Kubu, Seminyak. The population in this study were adult men and women over 18 years of age, who knew about Kubu Seminyak villa and had never stayed at kubu seminyak villa. The data analysis technique used in this study is Multiple Linear Regression, Coefficient of Determination, t test and F test using SPSS. Based on the results of the study where the count value is 75.469> 3.09 and the significance value of 0.000 <0.05 indicates that location and price simultaneously have a significant effect on buying interest. Based on the results of the coefficient of determination analysis, information was obtained that R Square was 0.609 or 60.9%. This value indicates that the independent variable is able to explain the dependent variable as much as 60.9%, while the remaining 39.1% is explained by other variables not included in this study. From the results of this study, it can be concluded that there is a positive and significant influence of location and price on buying interest.